Linear and Convergent Syntheses of Bifunctional Hydroxy-Bisphosphonic Compounds as Potential Bone-Targeting Prodrugs - Aoun, Sameh; Sierocki, Pierre; Lebreton, Jacques; Mathé-Allainmat, Monique (Synthesis, 2019)
The synthesis of two bifunctional compounds bearing a terminal hydroxy-bisphosphonic function (HBP) was achieved following a linear and a convergent strategy. In the linear approach, the free hydroxy-bisphosphonic function was introduced in the last step of the synthesis, under neutral conditions using an Arbuzov reaction with tris(trimethylsilyl) phosphite and a carboxylic acid precursor activated in situ with catecholborane. In the convergent approach, Huisgen type cycloaddition was studied starting from an HBP-functionalized alkyne partner to obtain the targeted bifunctional molecule. These complementary approaches allow for the preparation of complex bone-targeting molecules as potential prodrug candidates.
Keywords: bisphosphonate; Arbuzov reaction; click reaction; bifunctional derivatives; prodrug